2021
DOI: 10.1016/j.heliyon.2021.e07434
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of Vernonia amygdalina Delile against doxorubicin-induced cardiotoxicity

Abstract: Doxorubicin has been used as an anticancer drug and has already indicated effective in the treatment of cancer. The incidence of cardiotoxicity due to doxorubicin was approximately 11%, resulting in the limited use of doxorubicin. Cardiac protection during doxorubicin therapy is needed because it can reduce the incidence of heart failure. Vernonia amygdalina (VA) is traditionally used by Indonesians as a traditional medicine and contains many secondary metabolites, including vernolide, vernodalol, vernoamygdal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 41 publications
2
9
0
Order By: Relevance
“…In an in vivo study, CK-MB, LDH, and some specific cardiac biomarkers including BNP, Troponin T, and CRP were used to assess cardiotoxicity rate [118]. An agreement study by Syahputra showed that rats induced by doxorubicin significantly increased their BNP and Troponin T levels [119]. In some studies, the antioxidant was widely determined by the abundance of ROS production.…”
Section: Luteolinmentioning
confidence: 99%
“…In an in vivo study, CK-MB, LDH, and some specific cardiac biomarkers including BNP, Troponin T, and CRP were used to assess cardiotoxicity rate [118]. An agreement study by Syahputra showed that rats induced by doxorubicin significantly increased their BNP and Troponin T levels [119]. In some studies, the antioxidant was widely determined by the abundance of ROS production.…”
Section: Luteolinmentioning
confidence: 99%
“…However, its clinical applications are relatively restricted due to its detrimental side effects that include cardiotoxicity [2]. It was reported that the incidence of acute DOX cardiotoxicity is around 11%, which can be characterized on the electrocardiogram by decreased amplitude of QRS complexes and nonspecific ST changes [3,4]. This toxic damage to the cardiomyocytes induced by DOX can lead to the development of tachycardia, arrhythmia, pericarditis, myocarditis, left ventricular function transient depression, late-onset refractory cardiomyopathy, and, eventually, congestive heart failure [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Patients receiving doxorubicin exhibit left ventricular dysfunction demonstrated by elevated CK-MB and BNP activities ( Pongprot et al, 2012 ). Additionally, animal studies have reported increased CK-MB, LDH, BNP, and cTnT activities following doxorubicin administration ( Arafa et al, 2014 ; Kulkarni and Swamy, 2015 ; Nugraha et al, 2020 ; Syahputra et al, 2021 ). Moreover, previous research has also reported that doxorubicin elevates ALT ( Barakat et al, 2018 ); our findings support these previous ones of doxorubicin-induced clinical enzyme alterations.…”
Section: Discussionmentioning
confidence: 99%